Percepção dos alunos de 9º ano do Ensino Fundamental sobre o Ensino de Ciências - Polastreli, Valquiria (2020)
Teaching sciences has changed in Brazil and around the world, alternating its conceptions and finalities, following political processes, as well as technological, cultural and social. The School seeked adapting to these changes, aiming for the necessity o